Relationship between self-priming and hydraulic behavior in Venturi Scrubber - Naoki HORIGUCHI (The Japan Society of Mechanical Engineers, 2014)
As revealed by Fukushima Daiichi nuclear disaster, countermeasures against severe accident in nuclear power plants are an urgent need. In particular, from the viewpoint of protecting a containment and suppressing the diffusion of radioactive materials, it is important to develop the device which allows a filtered venting of contaminated high pressure gas. In the filtered venting system that used in European reactors, so called Multi Venturi Scrubbers System is used to realize filtered venting without any power supply (Lindau, 1988) (Rust, et al., 1995). The system operates with any power supply and high pressure gas filled in the containment. This system is able to define to be composed of Venturi Scrubbers (VS) and a bubble column. In the VS, scrubbing of contaminated gas is promoted by both gas releases through a submerged VS and gas-liquid contact with splay flow formed by liquid suctioned through a hole provided by the pressure difference between inner and outer parts of a throat part of the VS. This type of the VS is called self-priming ones. However, the scrubbing mechanism of the self-priming VS including effects of gas mass flow rate and shape of the VS are understood insufficiently in the previous studies. In this study, to understand the VS operation characteristics for the filtered venting, we discussed the mechanisms of the self-priming phenomena and the hydraulic behavior in the VS. In this paper, we conducted a visualized observation of the hydraulic behavior in the VS and measured liquid flow rate of the self-primming. As a result, it is shown that there is the possibility that the VS decontamination performance falls low level with no self-priming.